2023
DOI: 10.22541/essoar.167591090.06551819/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Surface Roughness Changes on Surface Wind Speed  over Western Europe: A Study with a Regional Climate Model            

Abstract: The temporal trend of wind speed near the surface over land has been investigated over recent decades. A prevailing trend of decline was found in several studies for most areas in the Northern hemisphere, denoted as terrestrial stilling, with multiple causes being discussed. In this study, we focus on the impact of changes of surface roughness due to changes in land-use and vegetation cover on this variable for western Europe using the regional climate model RACMO driven by ERA5 reanalysis. We conduct two simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…• How is this influenced by climate model, land use and exposure dataset choices? (Luu et al, 2023).…”
Section: How Uncertainty To Exposure Of Extreme Weather Hazards Affec...mentioning
confidence: 99%
See 1 more Smart Citation
“…• How is this influenced by climate model, land use and exposure dataset choices? (Luu et al, 2023).…”
Section: How Uncertainty To Exposure Of Extreme Weather Hazards Affec...mentioning
confidence: 99%
“…Results of further study on the relative roles of hazard versus exposure uncertainty are intended to be published, aiming to answer the important remaining research questions: How does climate change impact the largest European windstorms and their associated risk to society based on changes in hazard and exposure? How is this influenced by climate model, land use and exposure dataset choices? (Luu et al ., 2023). …”
Section: How Uncertainty To Exposure Of Extreme Weather Hazards Affec...mentioning
confidence: 99%
“…Surface wind speed is essentially regulated by surface properties. For instance, global surface wind slowdown over the past few decades had been extensively attributed to increased surface roughness caused by land use changes and urbanization (Chen et al, 2020; Luu et al, 2023; Minola et al, 2022; Vautard et al, 2010; Wang et al, 2020). Actually, Mohammed et al (1999) and Han et al (2016) reported that irrigation could promote crop growth and also decrease surface wind speed through increasing surface friction.…”
Section: Introductionmentioning
confidence: 99%